(untitled) (International Journal of Educational Management, Rivers State University., 2025)
The study sought to investigate the relationship between School-Community Partnership and Effective Implementation of Financial Accounting Curriculum in Secondary Schools in Omuma Local Government Area of Rivers State. Two research questions and hypotheses guided the study. Correlational research design was adopted for the study. The area of the study was Omuma Local Government Area of Rivers State. The population of the study comprised 104 teachers in Secondary Schools in Omuma. The entire population was studied because the population was manageable. Two self-made questionnaires titled: “Questionnaire on School Community Partnership (QSCP) and Questionnaire on Effective Implementation of Financial Accounting Curriculum (QEIFAC)” were used to collect data for the study. Three experts, one in Measurement and Evaluation and two in Business Education Department of Rivers State University validated the instruments. The Cronbach Alpha Method was used to ascertain the reliability coefficients of the instruments which yield 0.86. A total of 104 questionnaires were administered and 101 were completely filled and returned for the study. Pearsons Product Moment Correlation Coefficient (PPMCC) statistics was used to answer the research questions and test hypotheses. Finding showed that the relationship between availability of educational resources and effective implementation of financial accounting curriculum is moderately positive. It was recommended amongst others that school heads should ensure good community relationship as this could help mobilize community members to increase their participation in school management particularly in the area of promoting financial support and literacy education to the school.